Openness In Governance: The Effect of the E-Government Index on Regulation Quality in Australia - Anggita, Irva; Endang Indri Listiani; Yujitia Ahdarrijal (JOURNAL OF GOVERNMENT SCIENCE, 2025)
This research explores the relationship between the E-Government Development Index (EGDI) and the Quality of Government Regulation in Australian states. This study uses a quantitative approach with exposure to literature studies through Scopus and analyzes primary and secondary data. This research produced Online Service Index (OSI) p-values (0.388), E-Participation Index (EPI) p-values (0.764), Human Capital Index (HCI) p-values (0.000), and Telecommunication Infrastructure Index (TII) p-values (0.000) as predictors of Regulatory Quality (RQ). The use of the Smart PLS version 3 method and reliability and validity tests demonstrate the reliability of the proposed model. Statistical analysis yielded interesting results: EPI and OSI had no significant effect on RQ, while HCI and TII had a positive and significant relationship. These results provide insight into the factors influencing Regulatory Quality in the context of E-Government in Australia, supporting policy development to improve the efficiency and quality of public services. The research also contributes to an understanding of the impact of EGDI on governance and regulation at the state level.